2009
DOI: 10.1002/elps.200800225
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CpG methylation of the SNRPN gene by methylation‐specific multiplex PCR

Abstract: In this article, we show that methylation-specific multiplex PCR (MS-multiplex PCR) is a sensitive and specific single assay for detecting CpG methylation status as well as copy number aberrations. We used MS-multiplex PCR to simultaneously amplify three sequences: the 3' ends of the SNRPN gene (for unmethylated sequences), the KRITI gene (as internal control), and the promoter of the SNRPN gene containing CpG islands (for methylated sequences) after digestion with a methylation-sensitive restriction enzyme (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The detailed procedures were described previously [Hung et al, 2009]. LightCycler 480 software, version 1.3 (Roche, Basel, Switzerland) was used to analyze the data: the Y-axis represents the derivative of fluorescence changes and the X-axis represents the temperature ( C).…”
Section: Methylation-sensitive High-resolution Melting (Ms-hrm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedures were described previously [Hung et al, 2009]. LightCycler 480 software, version 1.3 (Roche, Basel, Switzerland) was used to analyze the data: the Y-axis represents the derivative of fluorescence changes and the X-axis represents the temperature ( C).…”
Section: Methylation-sensitive High-resolution Melting (Ms-hrm)mentioning
confidence: 99%
“…All DNA was extracted from peripheral blood using the Chemagic DNA Blood Kit (Chemagen, Baesweiler, Germany), and the MethylCode Bisulfite Conversion Kit (Invitrogen, Carlsbad, CA) was used to treat the DNA (1 mg) with bisulfite according to the manufacturer's instructions [Hung et al, 2009].…”
Section: Bisulfite Modification Of Dnamentioning
confidence: 99%
“…Faivre et al (2009) recently reported that exons 24-32 represent a hotspot for neonatal MFS and severe forms of MFS. The purpose of this study was to evaluate FBN1 mutations in Taiwanese individuals by using denaturing high performance liquid chromatography (DHPLC) and multiplex ligation-dependent amplification (MLPA) (Liu et al, 1997;Matyas et al, 2002;Kosaki et al, 2005;den Dunnen & White, 2006;Howarth et al, 2007;Kozlowski et al, 2008;Hung et al, 2005Hung et al, , 2006Hung et al, , 2007Hung et al, , 2008aHung et al, , 2008bHung et al, , 2009. DHPLC can detect heteroduplexes of denatured and reannealed PCR amplicons, and has a highcapacity and low-costs.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this problem, we designed methylation-specific multiplex PCR to determine copy number changes and methylation status in a single tube. 21 Recently, the melting curve analysis system was considered a promising tool for detecting sequence variation by the use of a saturating double-stranded DNA dye. Methylation-specific PCR and quantitative melting curve analysis can discriminate between deletional and nondeletional PWS and AS, 22 and it is based on a single-step procedure.…”
Section: Discussionmentioning
confidence: 99%